Formulation and clinical evaluation of silymarin pluronic-lecithin organogels for treatment of atopic dermatitis - Mady FM; Essa H; El-Ammawi T; Abdelkader H; Hussein AK (Dove Medical Press, 2016)
Fatma M Mady,1,2 Hanaa Essa,2 Tarek El-Ammawi,3 Hamdy Abdelkader,2 Amal K Hussein2 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Taibah University, Medina, Saudi Arabia; 2Department of Pharmaceutics, Faculty of Pharmacy, Minia University, Minia, Egypt; 3Department of Dermatology, STDs, and Andrology, Minia University Hospital, Minia, Egypt Abstract: Silymarin is a naturally occurring flavonoid drug; evidence from recent research has highlighted its use as a potential treatment for atopic dermatitis (AD). Both poor water solubility and drug permeability have hindered the percutaneous absorption of silymarin. Formulation of silymarin into pluronic-lecithin organogel (PLO) basis for topical skin delivery is the main aim of this work. Six different PLO formulations were prepared containing various pluronic to lecithin ratios using two cosolvent systems of ethyl alcohol and dimethyl sulfoxide. Formulation 2 (20% pluronic and 3% lecithin) was found to be the optimal base for topical delivery of silymarin as it showed optimum pH, viscosity, drug content, and satisfactory in vitro silymarin permeation. The silymarin PLO formulation significantly relieved inflammatory symptoms of AD such as redness, swelling, and inflammation. These findings warrant the ability for application of these novel silymarin PLO formulations as a novel treatment for AD. Keywords: silymarin, pluronic lecithin organogel, atopic dermatitis, skin penetration